2001
DOI: 10.1021/ol010015h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DNA Cleavage Activity of a Novel Bleomycin A5 Glycoconjugate

Abstract: [structure in text] To explore the possibility of modifying bleomycin in a fashion that could alter its physiological distribution in a therapeutic setting, a new analogue of bleomycin has been prepared. This analogue is intended to target the asialoglycoprotein receptor on liver cells. Critically, despite the large C-substituent, the bleomycin conjugate was found to degrade DNA in the same fashion as bleomycin A(5) itself, and with only modestly decreased efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…β-Cyclodextrin was chosen based on its size [6 Å (height) by 12 Å (diameter), PDB ID 3CGT] (22), its water-soluble, non-ionic nature and a facile route to its synthesis. This molecule could be characterized by NMR spectroscopy in contrast to the controlled-pore glass beads or dendrimers used for a similar purpose in previous studies (19,21). Although we argue that β-cyclodextrin is sufficiently large to prevent intercalation, we have been unable to demonstrate the mode(s) of CD-BLM binding to DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Cyclodextrin was chosen based on its size [6 Å (height) by 12 Å (diameter), PDB ID 3CGT] (22), its water-soluble, non-ionic nature and a facile route to its synthesis. This molecule could be characterized by NMR spectroscopy in contrast to the controlled-pore glass beads or dendrimers used for a similar purpose in previous studies (19,21). Although we argue that β-cyclodextrin is sufficiently large to prevent intercalation, we have been unable to demonstrate the mode(s) of CD-BLM binding to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the chlorinated bithiazole tail was shown to be located in the minor groove of DNA by light-mediated DNA cleavage (18). An additional independent study by the Hecht group has also shown that BLM A5 tethered through its polyamine tail to either controlled pore glass (CPG) beads (19,20) or a dendrimer (21) can also cleave DNA. These attachments were designed to be sufficiently large to prevent binding of the bithiazole tail by partial intercalation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…distance of 1.38 Å which is similar to the C-C bond distances observed in the pyridyl rings (Table 2). Both the N (7) and N(8) atoms are planar showing a sum of three angles as 360 • . This unit is mono-cationic and aromatic with the positive charge being delocalized on N(7) or N(8), giving a resonance structure (Scheme 2).…”
Section: Crystal Structurementioning
confidence: 99%
“…The structural and functional aspects of the BLMs-DNA interactions have earlier been studied using various BLM analogs/conjugates to determine the specific roles of different domains. [4][5][6][7][8] In contrast, synthetic model iron complexes are rare, possibly due to the structural complexity of BLMs. [9][10][11][12][13][14][15] Scheme 1 Schematic structure of Bleomycins.…”
Section: Introductionmentioning
confidence: 99%